Inter-observer reliability using the General Movement Assessment is influenced by rater experience. (October 2021) - Peyton, C.; Pascal, A.; Boswell, L.; deRegnier, R.; Fjørtoft, T.; Støen, R.; Adde, L.
Abstract: Objective: To describe the inter-observer reliability of the General Movement Assessment (GMA) among a sample of infants at high-risk of cerebral palsy (CP) among raters with various levels of experience. Methods: Video assessments of 150 high-risk infants at 10–15 weeks corrected age were rated by three Prechtl GMA-certified observers with varied experience using the assessment. Videos were scored based on temporal organization of fidgety movements (FMs), presence of abnormal FMs, or absence of FMs. Inter-observer agreements were analyzed with Gwet's AC1 statistic. Results: We found fair to moderate agreement when subcategories of normal FMs (continuous and intermittent) were included (AC1 = 0.32–0.57) and moderate to near perfect agreement when normal categories of FMs were combined (AC1 = 0.60–0.95). Reliability was higher among observers with more experience using the GMA (AC1 = 0.57–0.98) than the observer with less experience (AC1 = 0.32–0.61). Conclusions: Caution may be warranted when the GMA is used to differentiate "continuous and intermittent" FMs temporal organization. The GMA is highly reliable among experienced raters when comparing normal FMs to other FMs categorizations. Highlights: Inter-rater reliability of the GMA at 10–15 weeks of age in high risk infants was found to be fair to almost perfect. Experienced raters had nearly perfect agreement when comparing normal FMs to other classifications. The amount of experience a rater has using the GMA may contribute to their reliability using the assessment.